1981
DOI: 10.1093/oxfordjournals.jbchem.a133591
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Reaction of Halorhodopsin Prepared under Low Salt Conditions1

Abstract: 1. Membrane fraction containing halorhodopsin was prepared from the lysate of a mutant strain of Halobacterium halobium, Y1, which is defective in bacteriorhodopsin synthesis. 2. Irradiation of the membrane with red light at 0 degrees C decreased the absorbance intensities over the whole range of 500--600 nm and a new absorption peak appeared at about 400 nm. This process was reversed either by irradiation with blue light or simply by incubation in the dark. The wavelength at which the red light-induced absorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…7). We have observed this phenomenon in intact membranes (8), and it has also been reported by Ogurusu et al (21). The changes at 275 nm may be caused by perturbation in the charge densities around aromatic residues or retinal (or both) or by a change in the interaction of these chromophores.…”
Section: Spectroscopy Rapid Transient Absorbance Changes Weresupporting
confidence: 82%
“…7). We have observed this phenomenon in intact membranes (8), and it has also been reported by Ogurusu et al (21). The changes at 275 nm may be caused by perturbation in the charge densities around aromatic residues or retinal (or both) or by a change in the interaction of these chromophores.…”
Section: Spectroscopy Rapid Transient Absorbance Changes Weresupporting
confidence: 82%
“…It was concluded from this (Lanyi, 1984b) that the retinal configuration in HRSZO.C1-is cis (perhaps 13-cis as in the photointermediates of bacteriorhodopsin), rather than all-trans as in the parent molecule (Smith et al, 1984;Alshuth et al, 1985;Maeda et al, 1985). Extraction and analysis of the retinal has demonstrated the 13-cis isomeric form in illuminated halorhodopsin when the pigment was trapped in a stable form during the illumination, either as the deprotonated product (Ogurusu et al, 1981) or as the oxime.2 Flash-induced difference spectra, based on experiments similar to those in Figure 1, are shown in Figure 2. The absorption changes are given as extinction changes, calculated from the magnitudes of the flash-induced absorption changes at the indicated wavelengths and the amount of pigment that photocycled.…”
Section: Resultsmentioning
confidence: 97%
“…For example, removal of Cl − from pHR causes a 20-nm red shift of the visible absorption band, while sHR shows a 10-nm blue shift upon removal of Cl − . 30,31 The former absorption change is a normal reaction that could be induced upon removal of a negative charge in the active site, as indicated by previous spectroscopic studies of BR in which a 30-nm red shift was observed upon protonation of Asp85 by acidification with sulfuric acid. 32 The red-shifted species of BR generated at acidic pH, usually called the acid blue form, has been reported to mimic the O intermediate occurring in the last step of its proton pumping cycle.…”
Section: Introductionmentioning
confidence: 86%